Non-isothermal drying kinetics of human feces - Somorin, Tosin Onabanjo; Fidalgo, Beatriz; Hassan, S.; Sowale, Ayodeji; Kolios, Athanasios; Parker, Alison; McAdam, Ewan; Tyrrel, Sean (Taylor & Francis, 2019)
The non-isothermal drying behavior and kinetics of human feces (HF) were investigated by means of thermogravimetric analysis to provide data for designing a drying unit operation. The effect of heating rate and blending with woody biomass were also evaluated on drying pattern and kinetics. At low heating rate (1 K/min), there is effective transport of moisture, but a higher heating rate would be necessary at low moisture levels to reduce drying time. Blending with wood biomass improves drying characteristics of HF. The results presented in this study are relevant for designing non-sewered sanitary systems with in-situ thermal treatment.
Keywords: drying; Kinetics; human feces; Nano Membrane Toilet; thermal analysis